Safety Investigation of Hazardous Materials Released from the Combined High Temperature Gas Cooled Reactor – Hydrogen Production Plant Using ALOHA Software - D. Priambodo; S Sunarko; W. W. Purwanto (PPIKSN-BATAN, 2021)
Safety Investigation of Hazardous Materials Released from The Combined High Temperature Gas Cooled Reactor (HTGR) – Hydrogen Production Plant Using ALOHA software has been carried out. Currently, most of studies for HTGR-hydrogen plant are focused only on the impact of hydrogen presence to the HTGR plant safety. Therefore, the objective of this study was to investigate the effect of the presence of natural gas and synthetic gas from Steam Methane Reforming hydrogen plant on the combine HTGR-Hydrogen production system using ALOHA software. Three selected hazardous materials: CH4, CO and H2 were analyzed. The selected potential hazards of the hazardous materials after leaking from the pipe were downwind suffocation/toxication, flammable area and blast area from vapor cloud explosion. Two types of parameter, i.e., meteorological dispersion (including wind speed, temperature, humidity, nuclear building air changes for day and night) and source release parameters (including pipeline length, and distance from the reactor building to the hydrogen plant), were selected for this study. The effects of the parameters on the hazard distance were then analyzed. The study shows that hydrogen detector needs to be installed at the plant to ensure safety of field operator. Furthermore, CO adsorber and H2 recombiner should be installed at the Reactor HVAC system for CO poisoning and H2 fire protection. Provision of a separation distance of more than 250 meters or construction of a blast barrier between the reactor building and the hydrogen plant is also recommended to protect the reactor from H2 explosion hazard.